Reactivity and Mobility of Metals in Wetlands - Alan L. Wright; K. Ramesh Reddy (EDIS)
SL-297, a 3-page fact sheet by Alan L. Wright and K.R. Reddy, discusses the role of metals in wetlands, their function, changes they undergo, and the potential hazards associated with their presence and accumulation in wetlands. Includes references. Published by the UF Department of Soil and Water Science, June 2009.